2022
DOI: 10.1093/pubmed/fdac092
|View full text |Cite
|
Sign up to set email alerts
|

The usefulness of YouTube videos on lung cancer

Abstract: Background The use of social media as a source of health information is increasing, and the usefulness of the content may vary depending on the specific disease. Thus, this study was designed to assess the content, viewer engagement and usefulness of the most viewed YouTube videos on lung cancer. Methods 167 videos were reviewed, and 143 met the eligibility criteria. Two authors evaluated the videos separately, and data on vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
0
1
1
Order By: Relevance
“…Diers et al [31] reported that the videos of uploaders other than healthcare professionals were more popular. Meteran et al [30] determined that misleading videos were more popular (30). In contrast, in our study, there was no significant difference between the upload source groups in terms of total views, video length, time since upload, daily views, VPI, comprehensiveness score, or total video score.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Diers et al [31] reported that the videos of uploaders other than healthcare professionals were more popular. Meteran et al [30] determined that misleading videos were more popular (30). In contrast, in our study, there was no significant difference between the upload source groups in terms of total views, video length, time since upload, daily views, VPI, comprehensiveness score, or total video score.…”
Section: Discussioncontrasting
confidence: 83%
“…In the literature, different rates of usefulness have been reported concerning YouTube videos on different subjects. For example, the rate of useful videos was found to be over 60% for those with spondylarthritis [29], 62% for those with lung cancer [30], 65.4% for those with asthma [31], and 22% for those on endoscopic transsphenoidal surgery [32]. In addition, Esen et al [26] reported the rate of useful videos to be [26].…”
Section: Discussionmentioning
confidence: 99%